THE PLACES OF FRANZ PASSOV AND RICHARD TRENCHES IN 19th CENTURY LEXICOGRAPHY - Ulugbek Bahadirovich Rahmonov (Zien Journals, 2024)
In this article, the ideas and views of the European lexicographers F. Pasov and R. Trench, who laid the groundwork for the creation of the Big Oxford Dictionary, and the basic guidelines for the completion of the dictionary are highlighted
Keywords: Lexicographer; quote; principle; language